Clinical and endocrinological profile of children with precocious puberty at a tertiary care center (Indian Journal of Child Health, 2019)
Introduction: Puberty is said to be precocious if it appears before chronological age of 8 years in girls and 9 years in boys. Untreated early puberty leads to early sexual maturation with growth and bone age advancement with early fusion, leading to the paradox of tall stature in childhood but short adult final height. Objective: The objective of this study was to study the profile of precocious puberty in children with respect to clinical and endocrinological outcome. Materials and Methods: This was a prospective study of 28 children (23 girls) who presented with precocious puberty in pediatric endocrine outpatient department. Presenting complaints, clinical findings including anthropometry, investigations (biochemical and radiological), treatment, and outcome with follow-up visits (every 3 monthly), were recorded. Results: Age at the presentation was 5.4±2.6 years. Most common presentation in girls was breast development (82.6%) followed by axillary hair development (39.13%), pubic hair development (30.43%), vaginal bleeding (13%), and clitoral hypertrophy (4.3%). History of recent height spurt was reported in 69.57% of girls. Boys presented with pubic hair growth and increased penile length (100%), change in voice (40%), seizures, or behavioral issues including aggressiveness. Etiology varied with the idiopathic cause constituting majority of the cases in girls (43.5%) with other causes being ovarian tumor (4.3%), adrenal adenoma (4.3%), and thelarche variant (4.3%). In boys, hypothalamic hamartoma (60%) was the most common cause followed by sex cord tumors (40%). The mean advancement in bone age on presentation was 3.4 years. Baseline luteinizing hormone (LH) was found to be high in patients with central causes like hypothalamic hamartomas than in children with other cause. Gonadotropin-releasing hormone (GnRH) stimulation test was positive (maximal stimulated LH after aqueous GnRH analog >3 mIU/ml by chemiluminescence immunoassay) in 61.5% of patients. Height velocity post-treatment showed a declining trend as compared to previous records before the onset of treatment and bone age advancement also slowed down. Conclusions: Increasing trend of precocious puberty and its adverse effect on final height and psychological profile of patients mandates the need for early referral and diagnosis and appropriate management.